Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Problem Based Learning Pada Pembelajaran Tematik Terpadu Di Sekolah Dasar - Ranianisa Rahmi; Yeni Erita; Feby Kurniawan; Vani Qhairumnisa Utami (Journal on Education, 2023)
The low student learning outcomes inspired this study. The goal of this study was to show how the Problem Based Learning paradigm improved student learning outcomes in integrated theme learning for fifth grade students at SDN 43 Dadok Tunggul Hitam in Padang City. Classroom action research (CAR) employs both qualitative and quantitative methodologies. Teachers served as observers, researchers served as practitioners, and 27 fifth-grade kids (15 male students and 12 female students) participated in this study. Cycle I results on lesson plans averaged 76.79% (excellent), increasing to 92.85% (very good) in cycle II. The first cycle of teacher activity implementation averaged 80.35% (good), increasing to 96.42% (very good) in the second cycle. The first cycle's implementation on student activities averaged 76.79% (excellent), increasing to 96.42% (very good) in the second cycle. Student learning outcomes in cycle I averaged 60.34 (sufficient), rising to 88.85 (excellent) in cycle II. As a result, the Problem Based Learning (PBL) paradigm can be used to improve student learning outcomes in integrated thematic learning in elementary schools.